Implementación de una estrategia de capacitación para el uso adecuado de la tecnología biomédica en el municipio de Bolívar Cauca perteneciente a la E.S.E Sur Occidente, enfocado al personal de salud (2023)
The proposal arises from the interest of the E.S.E Sur Occidente in the Department of Cauca in the municipality of Bolívar, in search of excellence in the management and use of the biomedical equipment of the medical and assistance personnel of the related units. Biomedical technologies are intended to improve the quality, efficacy, and safety of patient care, however, incidents and adverse events may occasionally occur due to unsafe use, therefore appropriate staff measures must be taken to prevent such events, such as training. In the E.S.E Sur Occidente of the municipality of Bolívar Cauca, biomedical technology is a fundamental axis in care, which requires the appropriate use of technology. The purpose of this project is to promote patient safety and provide a quality service, for which a training strategy on the safe use of biomedical technology has been developed. With the support of the biomedical engineering department of the hospital establishment as well as the nursing staff for the conception, implementation and evaluation of the training program, the following was considered: The annual inventory of the care unit on biomedical equipment was analyzed, after this the adequate information of these is verified and the teams that are going to enter the training plan are pre-selected. The strategy was developed adapting to the needs of the E.S.E Sur Occidente belonging to Bolívar Cauca and the educational material is designed, which are the quick guides to carry out the training. Tests were carried out before and after each training, continuous monitoring was carried out in each area and a satisfaction survey was carried out with the strategy. Some recommendations for the frequency of training and the perception of the users were generated